The effectiveness of health promotion materials and activities on breastfeeding outcomes - Pannu, Poonam; Giglia, Roslyn; Binns, Colin; Scott, J.; Oddy, W. (Wiley-Blackwell, 2010)
Aim: To determine the effect of mothers receiving health promotion material and education antenatally and/or postnatally on breastfeeding outcomes in Perth, Western Australia. Methods: A 12-month longitudinal study was conducted in two public maternity hospitals in Perth, Western Australia, between 2002 and 2003. Data were collected on a consecutive sample 587 mothers. Results: The results showed that mothers who received an individual consultationor were involved in a discussion on breastfeeding antenatally with hospital staff were approximately 55% less likely to cease fully breastfeeding (HR 0.44; 95% CI 0.24–0.88) before 6 months, and 50% less likely to cease any breastfeeding before 12 months postnatally (HR 0.51; 95% CI 0.28–0.92). In the postnatal period, mothers who received instruction on positioning and attachment of the infant to the breast while in hospital were approximately 30% less likely to cease fully breastfeeding before 6 months (HR 0.66;95% CI 0.45–0.99).